Utilization of Treg Cells in Solid Organ Transplantation - Juneja, Tanya; Kazmi, Maria; Mellace, Michael; Saidi, Reza F. (Frontiers in Immunology, 2022)
Organ transplants have been a life-saving form of treatment for many patients who are facing end stage organ failure due to conditions such as diabetes, hypertension, various congenital diseases, idiopathic diseases, traumas, and other end-organ failure. While organ transplants have been monumental in treatment for these conditions, the ten year survival and long-term outcome for these patients is poor. After receiving the transplant, patients are put on a multi-drug regime of immunosuppressants. These drugs include cyclosporine, tacrolimus, corticosteroids, and antibodies. Polyclonal antibodies, which inhibit the recipient’s B lymphocytes, and antibodies targeting host cytokine inhibitors which prevent T cell activation of B cells are often used. Use of these drugs suppresses the immune system and increases the risk of opportunistic pathogen infections, tumors, and further damage to the transplanted organs and vasculature. Many regulatory mechanisms are present in organs to prevent the development of autoimmune disease, and Tregs are central to that mechanism. Tregs secrete suppressive cytokines such as IL-10, TGFB, and IL-35 to induce regulation of T cells. Additionally, Tregs can bind to target cells to induce cell cycle arrest and apoptosis, and can inhibit induction of IL-2 mRNA in target T cells. Tregs also interact with CTLA-4 and CD80/CD86 on Antigen Presenting Cells (APCs) to prevent their binding to CD28 present on T cells. Due to their various immunosuppressive capabilities, Tregs are being examined as a possible treatment for patients that receive organ transplants to minimize rejection and prevent the negative outcomes. A number of studies in which participants were given Tregs after undergoing organ transplantations were reviewed to determine the efficacy and safety of using Tregs in solid organ transplantation to prevent adverse outcomes.